Development of an experimental facility to study drag reduction and heat transfer enhancement of water flow in a channel - Thng, Yuet Choon (Nanyang Technological University, 2020)
This report proposes enhancement methods to increase the heat transfer coefficient in drag reducing flows. Two variations of heat enhancement devices were employed to show the difference in varying increases of heat transfer capabilities with adjustments to different methods of passive heat enhancement techniques. The conservation of energy and in turn being cost efficient has been a key design factor. In pipe or flow systems, having to overcome friction against the fluids and the surface of the pipes has caused great loss in energy. From many past investigations, it is known that drag reducing additives can be added to a flow system to significantly reduce the frictional drag experienced by the flow. This has generously helped many industries to perform more efficiently. This report looks extensively at the effects of surfactants in flow systems. With the addition of surfactants as drag reducing additives, the heat transfer capabilities of the flow are reduced substantially. However, this resulted in heat transfer inefficiencies in industries such as the district heating and cooling. However, with the addition of heat enhancement devices just before the heat exchanger, the heat transfer capabilities would increase. With the addition of vortex generator as a heat enhancement device, an increase of 50% in the heat transfer coefficient was observed. The vortex generator disrupts the flow generating vortices to stir up the flow and massively increase the heat transfer rate of the flow. The rod-like structures acting as flow disrupters also increased the heat transfer coefficient by 21.8%.